My Prosthetic Knee is Becoming Unstable - Lik Han, ONG; Sabaruddin, A.; Rutel, A.; Jaffar, MSA; Bong, CH; Tan, KT; Reuben, P.R; Kamaruddin, F. (MALAYSIAN ORTHOPAEDIC ASSOCIATION, 2022)
Total knee arthroplasty (TKA) has becoming one of most common surgical procedure with good outcome, pain reduction and vastly improve lifestyle of ageing population today with over 10,000 cases done yearly in Malaysia. The uptrend of this surgical procedure results in increasing complications and peri-prosthetic fracture is estimated to range between 0.3 to 2.5% of TKA complications.